2012
DOI: 10.1158/2159-8290.cd-11-0240
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Tumor Invasion and Metastasis by Concurrent Inhibition of c-Met and VEGF Signaling in Pancreatic Neuroendocrine Tumors

Abstract: Invasion and metastasis increase after inhibition of vascular endothelial growth factor (VEGF) signaling in some preclinical tumor models. The present study asked whether selective VEGF inhibition is sufficient to increase invasion and metastasis and whether selective c-Met inhibition is sufficient to block this effect. Treatment of pancreatic neuroendocrine tumors in RIP-Tag2 mice with a neutralizing anti-VEGF antibody reduced tumor burden but increased tumor hypoxia, HIF-1α, and c-Met activation, and also in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
369
4
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 358 publications
(402 citation statements)
references
References 62 publications
23
369
4
4
Order By: Relevance
“…Gene expression profiling of patient tumor samples and functional studies on tumor xenografts revealed that MET signaling is a key regulator of PanNET growth. Others have found that MET is a principal regulator of tumor aggressiveness of PanNETs in mice and human cell lines (19). Aberrant expression of MET has been observed in many solid tumors, yet most rely on activation of MET signaling by HGF (30).…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression profiling of patient tumor samples and functional studies on tumor xenografts revealed that MET signaling is a key regulator of PanNET growth. Others have found that MET is a principal regulator of tumor aggressiveness of PanNETs in mice and human cell lines (19). Aberrant expression of MET has been observed in many solid tumors, yet most rely on activation of MET signaling by HGF (30).…”
Section: Discussionmentioning
confidence: 99%
“…Une augmentation de la concentration intracellulaire en Ca 2+ est également à l'origine de la migration et de la prolifération des cellules progénitrices [28]. Des activations indirectes de voies impliquant STAT3 (signal transducer and activator of transcription 3) ou le récepteur de type tyrosine kinase c-MET, sont également observées dans les cellules tumorales à la suite d'une hypoxie intratumorale, participant au processus de résistance de la tumeur aux traitements antiangiogéniques [28,29]. La comparaison de l'analyse transcriptomique de glioblastomes résistants au bevacizumab avec d'autres, sensibles au traitement, issus d'un même patient, révèle une surexpression de c-MET.…”
Section: Les Autres Voies De Signalisationunclassified
“…[38]. Ces pompes sont en effet exprimées à la surface des cellules endothéliales isolées de xénogreffes de cellules tumorales humaines (lignée MDA-MB-435) dans des souris nudes (dépourvues de système immunitaire) pré-traitées avec des petites doses de doxorubicine avant l'expression de plusieurs chimiokines proangiogéniques comme CXCL7 [30], CXCL8 ou IL-8 [29], et de leur récepteurs CXCR1-2, exprimés par les cellules endothéliales mais aussi au niveau des cellules tumorales et des cellules du système immunitaire, est observée [18,30]. La lymphangiogenèse tumorale, via la surexpression du VEGFC, est égale-ment accrue.…”
Section: Directions Futures Pour Les Traitements Antiangiogéniques Leunclassified
“…In a study of 7 patients with KRAS wildtype metastatic CRC who initially responded to EGFR monoclonal antibody (mAb) panitumumab-or cetuximab-based treatment and then relapsed, 3 patients developed MET amplification [24]. More recent studies have identified a critical role of MET in anti-angiogenesis therapy-associated acceleration of tumor metastasis, and MET blockade significantly attenuated tumor metastasis to local lymph nodes and distant organs in breast cancer, melanoma, and pancreatic neuroendocrine tumor models [25,26].…”
Section: Met Activation As Resistance Mechanismmentioning
confidence: 99%